MARYAM PRENATAL EXERCISE AS AN EFFORT TO INCREASE CONTRACTION STRENGTH AND ACCELERATE LABOR DURATION - Neng Kurniati; Suharyo Hadisaputro; Rr. Sri Endang Pujiastuti; Ari Suwondo (Poltekkes Kemenkes Bengkulu, 2023)
Prolonged labor duration is associated with increased morbidity and mortality. Prenatal exercise has been shown to affect labor but has very low effectiveness on labor duration. Salat has been shown to affect fitness and health and has a rehabilitative impact. Maryam prenatal exercise is a modification of basic movements of prenatal exercises with postural bowing, sitting, and prostration in salat accompanied with dhikr. This study aims to prove the effect of Maryam prenatal exercise on pregnant mothers on the strength of contraction and labor duration. This study is a true experiment with a control group and a post-test-only design approach. The research was conducted at the Independent Midwife Practice at Sleman Regency, Yogyakarta on 2019. The sample amounted to 24 primigravida mothers with gestational age of > 32 weeks (1 sample dropout), and divided into control and intervention groups determined by randomization with a single-blinded approach. The intervention was conducted 3 times a week for 4 weeks, and the control group with basic prenatal exercises. This study showed the result that Maryam prenatal exercises have a significant effect on the 1st stage (p=0.000), the 2nd stage (p=0.000), and the strength of contraction (p=0.003). This study has no significant effect on the 3rd Stage of labor duration.